2012
DOI: 10.1002/jmri.23796
|View full text |Cite
|
Sign up to set email alerts
|

Motion artifact reduction of diffusion‐weighted MRI of the liver: Use of velocity‐compensated diffusion gradients combined with tetrahedral gradients

Abstract: The use of a t-VC-DWI sequence enables us to correct ADCs of the liver for artificial elevation due to cardiac motion, with preserved SNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 23 publications
7
46
0
Order By: Relevance
“…If motion artefacts are suppressed, higher intensities are revealed in the ROI and with higher signal-to-noise ratio (SNR), and we found that the alginate mould suppressed deformation, magnetic susceptibility artefacts and improved the SNR of images3233. Secondly, coil load is another factor that could affect the SNR of an image.…”
Section: Discussionmentioning
confidence: 84%
“…If motion artefacts are suppressed, higher intensities are revealed in the ROI and with higher signal-to-noise ratio (SNR), and we found that the alginate mould suppressed deformation, magnetic susceptibility artefacts and improved the SNR of images3233. Secondly, coil load is another factor that could affect the SNR of an image.…”
Section: Discussionmentioning
confidence: 84%
“…Flow‐compensation of the unweighted (b 0 ) image as performed in the work at hand might facilitate accurate determination of the perfusion fraction because the bipolar signal exhibits strong decay already at very small b‐values in case of a strong IVIM effect. Flow‐compensated diffusion gradients were, furthermore, found to improve image quality by reduction of motion artifacts in the liver and in cardiac imaging .…”
Section: Discussionmentioning
confidence: 99%
“…This can be overcome by performing DWI acquisitions at diastole using an ECG or pulse trigger 46 , but this approach results in significantly increased scan time. Another promising approach to mitigate signal loss due to cardiac motion is to use motion-compensated diffusion gradients 47,48 to cancel the dephasing of coherently moving tissues while maintaining diffusion-weighting.…”
Section: Dwi Techniquementioning
confidence: 99%